Multiple defects in a piezoelectric half-plane under electro-elastic in-plane loadings. (October 2019) - Bagheri, R.; Ayatollahi, M.; Mirzaei, A.M.; Monfared, M.M.
Highlights: Stress analysis is carried out in a piezoelectric half-plane with several defects containing a Volterra-type climb and glide edge dislocations. A close-form solutions of the edge dislocations is obtained using Fourier transform. The distributed dislocation technique is used to construct integral equations for a half-plane. These integral equations solved numerically to obtain the fields intensity factors at the crack tips. The effects of the cracks length, cracks interactions, geometrical parameters and loading conditions on the field intensity factors are studied. Abstract: This paper provides an analytical approach to calculate mixed-mode field intensity factors of multiple defects in a piezoelectric half-plane. Both the permeable and impermeable boundary conditions are adopted. In this study, the crack problem analysis caused by climb, glide and electric dislocation in the piezoelectric half-plane. The Fourier transform is employed and close-form solutions are obtained for the stress and electric displacements in the medium. Then, the solutions are used to derive singular integral equations for the dislocation density on the face of multiple cracks. These equations are solved numerically to determine the field intensity factors in a piezoelectric half-plane. Finally, several examples are solved and the effects of the cracks interactions, geometrical parameters and loading conditions are investigated.